Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Prerequisites - p.4 - Factoring Polynomials - Exercises - Page 39: 29



Work Step by Step

Expression : $27x^{3}+8 = (3x)^{3}+2^{3}$ By the well known formula : $x^{3}+y^{3}=(x+y)(x^{2}-xy+y^{2})$ Hence, $27x^{3}+8=(3x)^{3}+2^{3}=(3x+2)((3x)^{2}-3x(2)+2^{2})=(3x+2)(9x^{2}-6x+4)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.